The Analysis Power of the Main Character of Film Killers of the Flower Moon - Fani Tampang Bimbin; Bahar Bahar; Fitriana Fitriana (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study analyses the concept of power as portrayed by the main characters of Killers of the Flower Moon, focusing on how different types of power affect the dynamics of the story. Using French and Raven’s (1959) theory of power as an analytical framework, this study examines coercive power, referential power, and expert power as used by William Hale to manipulate and control the Osage people. This study uses qualitative descriptive methods, analyzing dialogue and scenes from the film script to identify patterns of power dynamics. The findings reveal that coercive power is used through intimidation, threats, and physical violence to enforce control, while referential power allows Hale to maintain his deceptive influence over the Osage people. In addition, expert power is abused by doctors and legal authorities to justify and cover up crimes against the Osage people. This analysis highlights the destructive effects of power when exploited for personal gain and shows how language and manipulation play a significant role in maintaining authority. Based on the results of the study, there are 30 total powers in the film, coercive power (10), referential power (10), and expert power (10). Ultimately, this study contributes to the understanding of power relations in media and literature, by emphasizing the relationship between social control, language, and oppression in historical narratives.